Limited evidence for white spot syndrome virus susceptibility associated with expression of PmVRP15 in local population of giant tiger shrimp (Penaeus monodon) - Aushia Tanzih Al Haq; M. Murwantoko; T. Trijoko; Nastiti Wijayanti; Ch. Retna Handayani; Rarastoeti Pratiwi (Indonesian Journal of Biotechnology, 2015)
White spot syndrome virus (WSSV) is a devastating viral disease in shrimp aquaculture. Infection ofWSSV in penaeid shrimps affects immune defense and changes gene expression. PmVRP15 has been reported as a part of the WSSV propagation pathway that is highly up-regulated in hemocytes at the acute phase of WSSV infection. This study analyzed the expression of PmVRP15 in local populations of giant tiger shrimp (Penaeus monodon) to be associated with susceptibility to WSSV. Tested populations consisted of an inbreeding population (G8) and outbreeding population (G8iA) from Jepara, Indonesia. Susceptibility was determined by cumulative mortality, median lethal time (LT50), and severity of infection at time of death. Though all populations were susceptible to WSSV, the frst mortality in G8 occurred at 18 hours post-infection (hpi) with mild infection, while frst mortality of G8iA occurred at 30 hpi with severe infection. The LT50 of G8 was signifcantly lower than that of G8iA, indicating that G8iA was less susceptible to WSSV than G8. Relative PmVRP15 transcripts of G8iA were insignifcantly down-regulated, whereas relative PmVRP15 transcripts of G8were insignifcantly upregulated. Although it’s still not conclusive, the results of this study suggest that PmVRP15 has weak potentialas a WSSV susceptibility marker in G8 and G8iA broodstock selection.